COMMUNICATIVE INTERACTION AS A COMPONENT OF PROFESSIONAL SKILLS OF THE FUTURE TEACHER OF TECHNOLOGY - O.I. Kopitsa (Academy of Cognitive and Natural Sciences, 2008)
The article is dedicated to the problem of forming the professionally significant communicative skills of would-be Handicraft teachers in the conditions of the introduction the educational field "Technology ".